POLYGONAL ARMS IN GRAND DESIGN SPIRALS - Chernin, A. D. (Одеські астрономічні публікації, 2017)
The phenomenon of polygonal arms in grand design spiral galaxies is reviewed. The Whirlpool Nebula, Messier 51 (NGC 5194) in Canes Venatici, is taken as an archetypical example. Optical photographs, Hα, UV and far-UV images, CO, 21 cm, sinchrotron emission maps, Ks-band mosaic of M 51 are used to recognize the global spiral pattern in M 51 which contains multiple straight arm segments and is presented by two polygons almost entirely. The polygons are almost identical, and the pattern has approximate twofold symmetry. The length of the straight arm segments is about the distance from the center of the disk. The segments intersect one another at the angle which is in average ≈ 2π/3. A brief list of galaxies with straight segments (M101 including) is given. The wave nature of the phenomenon is argued. A gasdynamical approach is discussed which implies that the formation of straight arm segments might be due to the generic stability of at shock fronts and the tendency of a slightly curved shock front to get at. A quantitative flattening criterion, based on this assumption, enables to explain the geometrical properties of the arm patterns found in M 51 and some other grand design spirals. Same considerations seem to be applicable to the ring structures that have a form of almost regular hexagons in a dozen disk galaxies.